Immediate skeletal effects of rapid maxillary expansion at midpalatal suture opening with Differential, Hyrax and Haas expanders - Alisson Gabriel Idelfonso BISTAFFA; Luciana BELOMO-YAMAGUCHI; Marcio Rodrigues de ALMEIDA; Ana Claudia de Castro Ferreira CONTI; Paula Vanessa Pedron OLTRAMARI; Thais Maria Freire FERNANDES (Dental Press Editora, 2023)
ABSTRACT Objective: The aim of this study was to test the null hypothesis that there is no difference at the midpalatal suture opening after rapid maxillary expansion (RME) using Expander with Differential Opening (EDO), Hyrax-type and Haas-type expanders. Methods: Occlusal radiographs of 52 patients (19 males and 33 females; average age= 9.46?1.20 years) treated with RME were divided into three groups, according to the expander used: EDO (n=17), Hyrax-type (n=21) and Haas-type (n=14). The evaluated variables were: A) Distance between the maxillary central incisors at the incisal edge; B) Distance between the alveolar ridges at the midpalatal suture; C) Suture opening at 10-mm distance from the crest to posterior, at the midpalatal suture; D) Suture opening at 20-mm distance from the crest to posterior, at the midpalatal suture; and E) Suture opening at 30-mm distance from the crest to posterior, at the midpalatal suture. To assess the normality of variables, the Shapiro-Wilk test was performed. For intergroup comparison, ANOVA with a significance level of 5% was used. Results: At the region A, Hyrax-type (4.66 mm) and EDO (4.87 mm) groups presented larger openings than the Haas-type group (3.43 mm). In regions B and C, EDO showed a statistically significant greater opening than the Haas-type group. In region D, a smaller opening of the midpalatal suture was observed in the Haas-type group, compared to the Hyrax-type and EDO groups. Conclusions: EDO and Hyrax-type produced greater immediate skeletal effects, compared with Haas-type, but these differences were about 1 mm and might not be clinically significant.